Coronary artery disease with type 2 diabetes and other risk factors: A tertiary care hospital in Bangladesh (Bangladesh Critical Care Journal, 2019)
Background: The aim of this study was to determine the prevalence of coronary artery disease (CAD) and to identify the various risk factors related to this complication in subject with diabetes.Methods: The study was cross-sectional and conducted in out-patients department of BIRDEM, from July 2016 to December 2017. Subjects were considered at age 30 to 70 years and duration of diabetes was 5-10 years. Investigations included socio-demographic (age, sex, education etc.), anthropometry (height, weight) and blood pressure. Blood samples were collected for HbA1c, fasting blood glucose (FBG), 2 hour after breakfast (2HABF), lipid profile and CAD were taken from the record books which was diagnosed by respective physician.Results: A total of 221 type 2 diabetes mellitus (T2DM) patients data were taken from the record books. There were 38 patients who had developed CAD and the prevalence of CAD was 17.2%. The study found that it had no significant difference between gender and CAD. The study also found that advanced age (OR=2.16;p=